Solution of Volume Integral Equation Using the SWG-Edge Hybrid Basis Functions for Inhomogeneous Dielectric Objects With Multiboundary - Zhang, Li-Ming; Deng, A-Li (IEEE transactions on antennas and propagation, 2021)
A hybrid discretization scheme for solution of volume integral equation (VIE) by method of moments (MoM) for electromagnetic scattering from dielectric objects is proposed in this article. The Schaubert-Wilton-Glisson and edge (SWG-Edge) hybrid basis functions are used in this discretization scheme. According to the divergence-free condition of electric displacement vector, a kind of edge basis functions defined in elements including boundary faces which separate a dielectric object from the background is derived. As a result, we get a SWG-Edge hybrid basis set. Details for the calculation of the corresponding matrix elements for the edge basis and testing functions are presented. Numerical results show the validity and accuracy of the hybrid discretization scheme. Finally, the proposed method is used for efficient solution of VIE for inhomogeneous dielectric objects with multiboundary. It is shown that for multiboundary problems, the number of unknowns of the hybrid basis is only about 71% of the traditional SWG basis. This means that the memory for solution of VIE by the traditional SWG basis functions can be reduced by half. Therefore, the SWG-edge hybrid basis is much more efficient than the traditional SWG basis for solution of VIE with multiboundary problems.